Analisis Penerapan Prinsip Good Corporate Governance Pada Penggunaan Dana Bantuan Operasional Sekolah - Rosydah, Faizatur; Ningtiyas, Nabilah Wahyu; Djasuli, Mohamad (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
With the application of the principles of good governance, the goal is to manage BOS funds in a way that meets their requirements. This is a critical requirement. The relationship mechanism between the various parties who manage the company as well as the "values" contained in the management mechanism itself are examples of Good Governance, a system of control and regulation for a business. The government's School Operational Assistance Fund (BOS) is used to cover educational units' operational expenses. Education management is the deliberate and planned process of creating a learning environment, enhancing the learning process, and achieving educational objectives. All educational units in Indonesia, not just regular schools, must have effective education management, and special schools (SLB) are no exception. A qualitative descriptive research approach is utilized in the research method. According to Dasor (2018), the application of the principles of Good Governance in the management of funds for School Operational Assistance (BOS) is the primary focus of this study. Some examples of this include: openness, responsiveness, participation, accountability, and fairness The methods used to collect the data were observation, interviews, and documentation studies. Interviews, field notes, and documentation provided the methods for data analysis. According to the findings of this research, the Tunas HarapanIII Mojoagung SLB school has implemented good governance principles in the school operational assistance fund (BOS).